Periplasmic Expression, Recovery and Quantification of Recombinant Human Interferon-A2b in Fermentation by Escherichia Coli - Ramanan, R. Nagasundara (2009)
Human interferon-α2b (IFN-α2b) is one of the biopharmaceuticals used to cure diseases such as hairy cell leukemia, malignant melanoma, and chronic hepatitis (B and C). Several areas related to the industrial problems, in the development of soluble IFN-α2b from recombinant Escherichia coli were explored in this study, which include enhancement of expression in periplasm, cell disruption techniques, quantification method and purification. The use of pET 26b(+) plasmid enhanced the periplasmic expression of IFN-α2b (300 ng/mL) by about 3000 times in E. coli RG 2(DE3) as compared to that obtained in the previous recombinant strain (0.1 ng /mL) using pFLAG-ATS plasmid. Difference in the expression level was attributed to the difference in the promoters and the signal sequences. In silico analysis suggested that the enhancement was mainly due to the difference in the translation initiation caused by mRNA secondary structure of the plasmid.The disruption of E. coli cells were investigated using glass bead shaking and homogenizer for small and large scale purpose, respectively. The optimum conditions for glass bead shaking were 30 min shaking at 300 rpm with 1.5 g/mL of glass beads (0.5 mm diameter). This technique was particularly useful for handling many samples at one time. The operating pressure range in a homogenizer was classified as low, transition and high pressures based on the characteristics of cell disintegrates. At low pressures, the protein release was mainly due to point break, which lead to high selectivity of IFN-α2b release. At higher pressures, the maximum release of total protein and IFN-α2b with a drastic reduction in cell size was observed after the first pass. Statistical optimization was used for osmotic shock process to release IFN-α2b at high concentration, with less process waste. Optimal process was achieved at cell concentration of 0.05 g/mL in hypertonic and 0.2 g/mL in hypotonic solutions. A rapid immunoassay method for quantification of IFN-α2b was developed using surface plasmon resonance technique. Anti-interferon monoclonal antibody (anti- IFN) was immobilized onto the CM5 chip using an amine coupling method. The perfect linearity was observed between 10 and 200 ng/mL. The anti-IFN chip was found to be useful for more than 1000 cycles and could also be used in continuous running environment. The efficacy of two activation methods using N-Hydroxysuccinimide in organic solvent (M I) and aqueous solution (M II) was assessed on CM Sepharose FF beads by immobilizing BSA onto it at various pH and ionic strengths. M I activation gave better immobilization efficiency than M II. Similar binding capacity was obtained with beads immobilized at pH 5 and 8 using anti-IFN; and with crude IFN-α2b as ligand and ligate. Knowledge gained from the molecular work gave better understanding of the expression pathway for future improvement of periplasmic IFN-α2b production by E. coli. Information and data obtained from this study were very useful for the development of efficient downstream and purification methods of IFN-α2b from E. coli fermentation at reduced cost, as well as simple and cheap quantification method for quality control and process monitoring.